2006
DOI: 10.1007/s10649-006-9036-2
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on a Theoretical Model to Study Students’ Understandings of Fractions

Abstract: Teaching and learning fractions has traditionally been one of the most problematic areas in primary school mathematics. Several studies have suggested that one of the main factors contributing to this complexity is that fractions comprise a multifaceted notion encompassing five interrelated subconstructs (i.e., part-whole, ratio, operator, quotient, and measure). Kieren was the first to establish that the concept of fractions is not a single construct, but consists of several interrelated subconstructs. Later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
190
0
35

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(233 citation statements)
references
References 13 publications
8
190
0
35
Order By: Relevance
“…The research by Charalambous, et al (2007) indicated that the concept of equivalence fractions helps students to work with the subconstructs of fractions and manage the operation of fractions more easily. Using the concept of ratio and table to teach division of fraction is shared by many researchers (Sharp 1998;Sharp 2002;Tirosh, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The research by Charalambous, et al (2007) indicated that the concept of equivalence fractions helps students to work with the subconstructs of fractions and manage the operation of fractions more easily. Using the concept of ratio and table to teach division of fraction is shared by many researchers (Sharp 1998;Sharp 2002;Tirosh, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these sub-constructs represents a different function of fractions. Some evidence suggests that this theoretical model lines up with the way in which students conceive fractions (Charalambous & Pitta-Pantazi, 2007), and the five sub-constructs have been widely accepted (Behr et al, 1993;Charalambous & Pitta-Pantazi, 2007;Kieren, 1976).…”
Section: Fractions Represent Five Different Constructsmentioning
confidence: 89%
“…Fractions do not represent one monolithic construct, rather researchers have identified five interrelated fraction sub-constructs: part-whole, ratio, operator, quotient, and measure (Behr, Harel, Post, & Lesh, 1993;Charalambous & Pitta-Pantazi, 2007;Kieren, 1976;Pantziara & Philippou, 2012). Each of these sub-constructs represents a different function of fractions.…”
Section: Fractions Represent Five Different Constructsmentioning
confidence: 99%
See 2 more Smart Citations